Basic guarantees for mental health in a pandemic scenario: reflections on psychological claims in health professionals (Research, Society and Development, 2021)
The working conditions and the way in which the individual gives meaning to it, can contribute to severe damage to mental health. Considering the current scenario, health professionals are daily subject to stressful events arising from their work process. The research aims to analyze possible implications for the mental health of health professionals in the pandemic scenario caused by COVID-19. To this end, the present study was developed based on bibliographic research, supported by research that addressed the issue of mental health related toworking conditions of health professionals in times of pandemic. From the data analysis, it can be seen that the current scenario and the demands faced in their work environment are established as contributing factors for the emergence of emotional damage and psychological implications for the health of health professionals. Thus, the support resources that help in the psychological support of the demands experienced by these professionals are essential in health services.